2020
DOI: 10.1021/acs.jpcb.9b09123
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Self-Assembling Behavior of Biological Building Block Molecules: A Spectroscopic and Microscopic Approach

Abstract: Metrics & MoreArticle RecommendationsABSTRACT: "Mother nature" utilizes molecular self-assembly as an efficient tool to design several fascinating supramolecular architectures from simple building blocks like amino acids, peptides, and nucleobases. The self-assembling behavior of various biologically important molecules, morphological outcomes, molecular mechanism of association, and finally their applications in the real world draw broad interest from chemical and biological point of views. In this present Fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 120 publications
0
25
0
Order By: Relevance
“…Recently, a great emphasis was given to the ability of amino acids to serve as building blocks for the formation of various supramolecular assemblies with attractive features ( Guerin et al., 2018 ; Ji et al., 2019 ; Makam et al., 2019 ). It was shown that single amino acids in their aggregated form can also produce a fluorescent signal, which is not evident in the monomeric state ( Babar and Sarkar, 2017 ; Banerjee et al., 2020 ; Niyangoda et al., 2017 ; Shaham-Niv et al., 2018 ). Numerous observations suggest that the optical phenomenon of aggregation-induced intrinsic fluorescence is broader than originally speculated, as it also applies to many other metabolites and nucleic acids ( Arnon et al., 2019 ; Berger et al., 2015 ; Chen et al., 2018 ; Lakowicz et al., 2001 ; Stephens et al., 2020 ; Zou et al., 2002 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, a great emphasis was given to the ability of amino acids to serve as building blocks for the formation of various supramolecular assemblies with attractive features ( Guerin et al., 2018 ; Ji et al., 2019 ; Makam et al., 2019 ). It was shown that single amino acids in their aggregated form can also produce a fluorescent signal, which is not evident in the monomeric state ( Babar and Sarkar, 2017 ; Banerjee et al., 2020 ; Niyangoda et al., 2017 ; Shaham-Niv et al., 2018 ). Numerous observations suggest that the optical phenomenon of aggregation-induced intrinsic fluorescence is broader than originally speculated, as it also applies to many other metabolites and nucleic acids ( Arnon et al., 2019 ; Berger et al., 2015 ; Chen et al., 2018 ; Lakowicz et al., 2001 ; Stephens et al., 2020 ; Zou et al., 2002 ).…”
Section: Introductionmentioning
confidence: 99%
“…The phenomenon of aggregation-dependent luminescence of proteins is a rapidly evolving field ( Ardona et al., 2017 ; Arnon et al., 2019 ; Babar and Sarkar, 2017 ; Banerjee et al., 2020 ; Berger et al., 2015 ; Bhattacharya et al., 2017 ; Chan et al., 2013 ; Kong et al., 2019 ; Niyangoda et al., 2017 ; Pansieri et al., 2019 ; Pinotsi et al, 2013 , 2016 ; Prasad et al., 2017 ; Shaham-Niv et al., 2018 ). Protein aggregates were shown to absorb light at wavelengths above 300 nm and to exhibit a structure-specific fluorescence in the visible range, even in the absence of aromatic amino acids ( Del Mercato et al., 2007 ).…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9] It was shown that single amino acids in their aggregated form can also produce a fluorescent signal, which is not evident in the monomeric state. [10][11][12][13] Numerous observations suggest that the optical phenomenon of aggregation induced intrinsic fluorescence is broader than originally speculated, as it also applies to many other metabolites and nucleic acids. [14][15][16][17][18][19] Circumstantial evidence and argumentation suggested that supramolecular packing is important.…”
Section: Introductionmentioning
confidence: 99%
“…The phenomenon of aggregation-dependent luminescence of proteins is a rapidly evolving field. 1,2,17,[22][23][24][3][4][5][10][11][12][13]16 Protein aggregates were shown to absorb light at wavelengths above 300 nm and to exhibit a structure-specific fluorescence in the visible range, even in the absence of aromatic amino acids. 6 A plausible explanation for this phenomenon is the formation of structure-specific supramolecular fluorophores that are permissive to proton transfer across hydrogen bonds.…”
Section: Introductionmentioning
confidence: 99%
“…16 Most of the studies of L-Phe self-assembly are conducted in approximately millimolar concentrations, as it is much more relevant to the diseased condition of PKU. 2,8 It is also observed that almost every investigation of L-Phe self-assembly considers the incubation of L-Phe solution for 1 d without any disturbance to ensure amyloid structure formation. 2,8 In the present work, it is found that L-Phe can form amyloid-like structures instantly after solution preparation, which is evident from highresolution transmission electron microscope (HRTEM) images (Figure 1a).…”
mentioning
confidence: 99%